1999
DOI: 10.1007/s005950050649
|View full text |Cite
|
Sign up to set email alerts
|

Malignant rhabdoid tumor of the colon: Report of a case

Abstract: A malignant rhabdoid tumor of the colon is very rare and only three cases have been previously described. A 76-year-old man was admitted to the hospital complaining of epigastralgia. An elastic mass was palpable in the right upper abdomen. A barium enema and endoscopic examination showed a giant gyrate tumor arising from the cecum. Abdominal ultrasonography and a computed tomography scan revealed the tumor to be located in the colon associated with multiple liver metastases and gallbladder stones. A right cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…Although the histogenesis of rhabdoid tumors is unknown, all reported cases share similar histological, immunohistochemical, and ultrastructural findings 3. The ultrastructural findings of the reported cases showed that the rhabdoid cells had eccentric nuclei containing prominent nucleoli and paranuclear inclusions composed of intermediate filaments of the mesenchymal cytoskeleton 8,9,12,13. Although the percentage of tumor cells with a rhabdoid morphology that are needed in a carcinoma to constitute a composite rhabdoid tumor is still up for debate, the percentage of rhabdoid tumor cells in previously reported cases have been greater than 60% 10,17.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the histogenesis of rhabdoid tumors is unknown, all reported cases share similar histological, immunohistochemical, and ultrastructural findings 3. The ultrastructural findings of the reported cases showed that the rhabdoid cells had eccentric nuclei containing prominent nucleoli and paranuclear inclusions composed of intermediate filaments of the mesenchymal cytoskeleton 8,9,12,13. Although the percentage of tumor cells with a rhabdoid morphology that are needed in a carcinoma to constitute a composite rhabdoid tumor is still up for debate, the percentage of rhabdoid tumor cells in previously reported cases have been greater than 60% 10,17.…”
Section: Discussionmentioning
confidence: 79%
“…There is a possibility that these two MSI-high tumors might not be associated with rhabdoid features but instead are associated with their right side colonic locations. The overexpression of the p53 protein, suggesting mutation of the p53 gene, was noted in four out of the 10 reported cases 7,8,11,13. In the remaining 6 cases, p53 protein results were not described.…”
Section: Discussionmentioning
confidence: 90%
“…In two cases of colonic MRT immunohistochemical p53 staining has been observed. 10,11 On ultrastructural examination, the cytoplasm of rhabdoid cells showed whorls of filaments in paranuclear areas, thus corresponding to the glassy hyaline masses visible under a light microscope. 3,12 Recently, these neoplasms have been shown to consistently demonstrate monosomy of chromosome 22 either with or without a partial deletion of the remaining companion chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 In some studies Ki-67 and/or proliferating cell nuclear antigen immunoreactivity is shown to be strongly positive in tumor cells, thus indicating a high proliferative activity. 8,10 The presence of p53 mutation in malignant renal rhabdoid tumor (MRRT) and MERT has yet to be elucidated. In two cases of colonic MRT immunohistochemical p53 staining has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Extrarenal rhabdoid tumors have now been reported in many organs, including the brain [9^11], eye [12], heart [13], liver [14], colon [15], tongue [16], bladder [17], prostate [18], vulva [19], uterus [20], skin [21], and soft-tissue from many sites such as the extremities [22], neck, mediastinum, retroperitoneum, pelvis, and paraspinal regions [23]. Some reported cases of extrarenal rhabdoid tumor have the same clinical pattern as their renal counterparts, including young age, early dissemination, and lethal outcome [5].…”
Section: Discussionmentioning
confidence: 99%